Higher education and equality of opportunities : cross-national perspectives - Lazin, Frederick A., 1943-; Evans, Matt, 1963-; Jayaram, N., 1950- (Studies in public policy (Lanham, Md.), 2010)
This volume provides a broad overview of recent higher education policy in a variety of countries, both developed and developing, around the world. Using interdisciplinary methods and analysis, it focuses on how diminishing governmental resources and expanding market forces influence higher education policy in different countries in terms of access, minority status (including ethnic, national and gender groups), affirmative action, quality, and performance.